Pluvial flood risk and opportunities for resilience. (17th July 2018) - Rosenzweig, Bernice R.; McPhillips, Lauren; Chang, Heejun; Cheng, Chingwen; Welty, Claire; Matsler, Marissa; Iwaniec, David; Davidson, Cliff I.
Abstract : The risk presented by pluvial flooding has emerged as a critical issue in urban water management. Pluvial flooding occurs when precipitation intensity exceeds the capacity of natural and engineered drainage systems, and it is expected to increase in frequency, severity and impact through the 21st century due to the combined effects of climate change and urbanization. Although there have been recent advances in approaches to assess the risk presented pluvial flooding and to enhance the resilience of cities to its impacts, they have not been broadly implemented and there are many opportunities for additional research. We provide case studies of pluvial flooding in six cities in the continental United States, which serve as examples of the current vulnerability of cities that have not developed comprehensive pluvial flood management plans and the challenges in conducting pluvial flood research in light of existing data gaps. We also identify key research challenges that should be prioritized by the interdisciplinary water research community to better support urban resilience practice. This article is categorized under: Engineering Water > Sustainable Engineering of Water Science of Water > Water Quality Engineering Water > Planning Water Abstract : Pluvial flooding.